A DNA Vaccine for Ebola Virus Is Safe and Immunogenic in a Phase I Clinical Trial - Martin, Julie E. (American Society for Microbiology, 2006)
Ebola viruses represent a class of filoviruses that causes severe hemorrhagic fever with high mortality. Recognized first in 1976 in the Democratic Republic of Congo, outbreaks continue to occur in equatorial Africa. A safe and effective Ebola virus vaccine is needed because of its continued emergence and its potential for use for biodefense. We report the safety and immunogenicity of an Ebola virus vaccine in its first phase I human study. A three-plasmid DNA vaccine encoding the envelope glycoproteins (GP) from the Zaire and Sudan/Gulu species as well as the nucleoprotein was evaluated in a randomized, placebo-controlled, double-blinded, dose escalation study. Healthy adults, ages 18 to 44 years, were randomized to receive three injections of vaccine at 2 mg (n = 5), 4 mg (n = 8), or 8 mg (n = 8) or placebo (n = 6). Immunogenicity was assessed by enzyme-linked immunosorbent assay (ELISA), immunoprecipitation-Western blotting, intracellular cytokine staining (ICS), and enzyme-linked immunospot assay. The vaccine was well-tolerated, with no significant adverse events or coagulation abnormalities. Specific antibody responses to at least one of the three antigens encoded by the vaccine as assessed by ELISA and CD4(+) T-cell GP-specific responses as assessed by ICS were detected in 20/20 vaccinees. CD8(+) T-cell GP-specific responses were detected by ICS assay in 6/20 vaccinees. This Ebola virus DNA vaccine was safe and immunogenic in humans. Further assessment of the DNA platform alone and in combination with replication-defective adenoviral vector vaccines, in concert with challenge and immune data from nonhuman primates, will facilitate evaluation and potential licensure of an Ebola virus vaccine under the Animal Rule.